PERUBAHAN SOSIAL BUDAYA SUKU BADUY LUAR: SEBUAH ANALISIS INTERAKSI ANTARA TRADISI DAN MODERNITAS - Yoga Mahendra; Gustini Wulandari; Lilis Lilis (LPPM Universitas Bina Bangsa, 2023)
The Outer Baduy community experiences relatively rapid social changes due to their less strict customary rules compared to the Inner Baduy. The purpose of this research is to describe how the Cultural and Social Changes of the Outer Baduy Tribe occur: An Analysis of the Interaction between Tradition and Modernity. The method employed in this research is the Descriptive research method with a qualitative approach, using observation sheets and documentation as research instruments. Data collection techniques used in this study include interviews and in-depth observations of the Outer Baduy community. The data sources consist of primary and secondary data. Data validation is conducted through data triangulation, and data analysis follows Miles and Huberman's model, which includes data collection, data reduction, data display, and conclusion drawing. The research findings indicate that the most notable socio-cultural changes occur due to shifts in livelihoods from farming to trading and the use of electricity-requiring technology. These changes happen because of economic needs, leading the Outer Baduy community to choose non-farming occupations, such as tourism-related jobs or trading, to fulfill their needs and even make it their primary source of income. Consequently, the Outer Baduy community consciously accepts and understands the impacts of technological modernization, information, and communication, whether direct or indirect